2021
DOI: 10.52041/serj.v20i1.100
|View full text |Cite
|
Sign up to set email alerts
|

Content Knowledge and Attitudes Towards Stochastics and Its Teaching in Pre-Service Chilean Mathematics Teachers

Abstract: Recognizing that mathematics teachers are facing increasing demands in the teaching of probability and statistics (stochastics) at school level, we are interested in analyzing current pre-service teachers’ dispositions about content knowledge and attitudes towards the teaching and learning of stochastics. We implemented a quantitative study for a sample of 269 pre-service Chilean mathematics teachers to determine their understanding of stochastics content, their attitudes towards stochastics and its teaching, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Attitudes have a stronger cognitive component than emotions and are relatively stable over time (Estrada & Batanero, 2020). Ruz et al (2021) found a positive association between content knowledge and attitudes of pre-service teachers, while Segarra and Julià (2022) also confirmed that teachers' efficacy beliefs as well as attitudes towards mathematics are key factors for pre-service teacher's mathematics academic achievement.…”
Section: Research Articlementioning
confidence: 67%
“…Attitudes have a stronger cognitive component than emotions and are relatively stable over time (Estrada & Batanero, 2020). Ruz et al (2021) found a positive association between content knowledge and attitudes of pre-service teachers, while Segarra and Julià (2022) also confirmed that teachers' efficacy beliefs as well as attitudes towards mathematics are key factors for pre-service teacher's mathematics academic achievement.…”
Section: Research Articlementioning
confidence: 67%
“…Similarly, Şafak (2016) identified student misconceptions about dependent-independent events in probability. Ruz et al (2021) observed in their study that preservice teachers were less successful in probability compared to other mathematics topics, and only one in five were able to provide correct answers to probability questions. Similar results were observed in different studies which concluded that preservice teachers had difficulties in understanding basic concepts about Probability (Arıcan & Kuzu, 2020; Garfield & Ben-Zvi, 2008, 2020; Koparan, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Common probability knowledge can be defined as the knowledge that is expected to be acquired by students from 8th to 12th grade in the education program of Turkey. In sum, preservice teachers should have the knowledge and concepts that are expected to be acquired by 12th-grade students (Ruz et al, 2021). This knowledge consists of the most basic information and concepts related to probability.…”
Section: Introductionmentioning
confidence: 99%
“…Esta investigación se enmarca dentro del enfoque cuantitativo y es un estudio exploratorio en el contexto chileno (Hernández et al, 2014). Se utilizó la Escala de Conocimiento del Contenido Estocástico Común y Ampliado (CESK) (Ruz et al, 2021), instrumento diseñado exclusivamente para este fin, validado previamente en términos de contenido por medio del juicio experto de 10 investigadores en educación estadística de Iberoamérica y una aplicación piloto con 126 futuros profesores de matemáticas de Chile y España, donde se analizó la consistencia interna del test y aspectos como la dificultad y discriminación de los ítems que lo conforman, como se detalla en Ruz et al (2020b). Los ítems tienen una adecuada dificultad (entre 10 y 90% de respuestas correctas), discriminación (coef.…”
Section: Metodologíaunclassified
“…En consecuencia, nos planteamos que las mayores problemáticas relativas al conocimiento del contenido y la enseñanza de la estocástica en profesores pueden ser abordadas reorientando su formación inicial en este tema (Ruz et al, 2021). En esta nueva mirada, además de profundizar en temas más avanzados de la estocástica que les permita a los profesores dar oportunidades a los estudiantes por aprender los conocimientos que van más allá de los contenidos curriculares, se debería promover un mayor compromiso, al menos, por lo temas que deban enseñar, considerando el desarrollo de habilidades vinculadas con las tareas propias del estadístico (Pfannkuch y Ben-Zvi, 2011) y con un fuerte apoyo tecnológico.…”
Section: Conclusionesunclassified